Seven Affordances of Computer-Supported Collaborative Learning: How to Support Collaborative Learning? How Can Technologies Help?. Issue 2 (2nd April 2016) - Jeong, Heisawn; Hmelo-Silver, Cindy E.
Abstract : This article proposes 7 core affordances of technology for collaborative learning based on theories of collaborative learning and CSCL (Computer-Supported Collaborative Learning) practices. Technology affords learner opportunities to (1) engage in a joint task, (2) communicate, (3) share resources, (4) engage in productive collaborative learning processes, (5) engage in co-construction, (6) monitor and regulate collaborative learning, and (7) find and build groups and communities. We elaborate our framework using in-depth explorations of how technologies are actually used to support collaborative learning in CSCL research and identify representative design strategies and technology examples. While technology can play an important role in addressing the demands of collaborative learning, it needs to be considered in conjunction with pedagogical strategies and other social and cultural supports for collaborative learning. The supports also need to remain at an appropriate level so as not to interfere with long-term learning goals.